Correlation analysis to identify DNA methylation and miRNA regulation toward IQGAP genes family. (March 2019) - Agustriawan, David; Aditya Parikesit, Arli; Nurdiansyah, Rizky
Abstract: The aberrant expression of IQGAP genes family which consist of IQGAP1, IQGAP2 and IQGAP3 is related with various kinds of cancer where IQGAP can function as oncogenes or tumor suppressor genes . The increasing number of the study suggested that upregulated or downregulated of IQGAP gene expression in cancer cell trigger the spreading of cancer. The model and function of the IQGAP1 gene have been investigating in many cancer types. However, study related IQGAP2 and IQGAP3 in cancer formation is still lack, and it needs to be further investigated. Moreover, epigenetic regulation related to the aberrant expression of IQGAP genes in cancer formation is not well studied yet. Therefore, this study conducted a correlation study to identify the interaction of IQGAP gene family expression with DNA methylation and miRNA expression in Ovarian cancer. This research was performed a correlation analysis which integrated miRNA, Gene and DNA methylation expression dataset. All the computation was calculated in MATLAB software. This study identified that IQGAP1 significantly negatively correlated with DNA methylation probe cg109784032 and forty-three miRNAs.